Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

1st order linear ODE

  1. Oct 17, 2006 #1
    Find the solution of the given initial value problem
    y'-y=2te^2t y(0)=1

    so p(t)=-1
    then [tex] \mu (t)= e^/int -1 dt= e^-t [/tex]
    e^-t y'-e^-t y=2te^2te^-t
    d/dt [e^-t y]=2te^t dt
    e^-t =[tex] \int 2te^t dt [/tex]
    e^-t y= 2te^t-2e^t
    plugging in the initial conditon gives me

    Am I doing this right? If not, can someone help?
  2. jcsd
  3. Oct 17, 2006 #2
    [tex] I = e^{-\int t} = e^{-t dt} [/tex].

    So you get [tex] ye^{-t} = 2\int te^{t} dt = 2te^{t} - 2e^{t} + C [/tex]

    [tex] y = \frac{2te^{t} - 2e^{t} + C}{e^{-t}} [/tex]

    [tex] y = \frac{2te^{t} - 2e^{t} + 2}{e^{-t}} [/tex]

    [tex] y = 2te^{2t} - 2e^{2t} + 2e^{t} [/tex]
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook